A nanocavity structure based on MDM

By setting adjustable notches in the MDM-type nanocavity structure and adjusting the radius of the silver nanoring, the shortcomings of spectral adjustment and absorption intensity adjustment in the prior art are solved, and efficient up-conversion luminescence enhancement and multi-band adjustability are achieved.

CN115372325BActive Publication Date: 2025-02-28HUNAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210810137.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-02-28
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

The existing MDM-type nanocavity structures have shortcomings in freely adjusting the intensity of the absorbing light source and adjusting the spectral range, and cannot achieve efficient upconversion luminescence enhancement and multi-band adjustability.

Method used

A composite material based on the MDM-type nanocavity structure is designed, including a silver nanoring layer, a UCNPs layer and a silver bottom layer. By setting adjustable notches on the silver nanoring layer and adjusting the radius of the silver nanoring, free adjustment of the absorption spectrum and enhancement of up-conversion luminescence is achieved.

Benefits of technology

The MDM-type nanocavity structure has achieved efficient absorption and adjustable absorption spectrum for light in a specific wavelength range, which improves the flexible control ability of the upconverted luminescent emission spectrum and significantly improves the luminescence intensity and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115372325B_ABST
    Figure CN115372325B_ABST
Patent Text Reader

Abstract

The present invention discloses an MDM-type nanocavity structure, which includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom; and on each silver nanoring of the silver nanoring layer, two gaps that can be opened or closed freely are symmetrically arranged, and the angle of the gap opening can be adjusted; and the absorption area and the up-conversion fluorescence enhancement factor value in the absorption spectrum can also be adjusted by changing the radius of the silver nanoring. Through the above settings, the MDM-type nanocavity can achieve efficient absorption of an external light source with a specific wavelength range, and the MDM-type nanocavity has an adjustable absorption spectrum within a specific wavelength range, that is, its absorption spectrum can achieve free absorption intensity adjustment, and the adjustment of the spectrum red shift or blue shift, and finally realize flexible control of the emission spectrum of up-conversion emission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resonant cavities, in particular to a MDM-type nanocavity structure. Background Art

[0002] Upconversion nanoparticles (UCNPs) are mainly inorganic nanomaterials doped with rare earth elements. They can convert near-infrared light into ultraviolet-visible light by utilizing the metastable energy level characteristics of rare earth elements. Due to their excellent photochemical stability, deep light penetration depth, long radiation lifetime, no background fluorescence interference and almost no damage to biological tissues, they play an important role in many fields including biomedicine, display technology and solar cells. However, there are still some disadvantages, such as the limitation of surface effects and lattice defects of nanomaterials, resulting in low luminescence intensity and thus weak light signals. In order to improve the luminescence efficiency, many solutions have been proposed, including the selection of matrix materials, adjustment of dopants and surface chemistry. In recent years, the research on upconversion luminescence enhanced by metal nanostructures through surface plasmon has received widespread attention, thanks to the high local field strength and spectral band matching.

[0003] However, most of the current structures have problems such as large scattering losses and low coupling efficiency, which limit the improvement of the overall luminescence enhancement factor. Therefore, it is very important to construct a composite material with efficient coupling and low loss of metal nanostructures and UCNPs. As early as 2009, H Giessen's group designed a three-layer metal dielectric structure that can confine near-infrared incident light to certain specific areas to form a strong local electromagnetic field. T Zhang et al. studied the narrow-band absorption characteristics of the MDM structure and conducted a theoretical analysis of its application in sensors. In 2019, X Liu's team reported the structure of an MDM-type composite nanocavity upconversion material, which achieved efficient enhancement of upconversion luminescence and exhibited a multi-color luminescence appearance, with the advantages of strong local fields and controllable plasma resonance characteristics. The above is a study on the matching of a single band. Now it has been reported that rare earth upconversion luminescent nanomaterials excited by 808nm / 980nm dual channels have unique advantages in biological precision detection and super-resolution fluorescence imaging. At the same time, it is found that the second near-infrared window (1000-1700nm) has better imaging quality and deeper tissue penetration than the first near-infrared window (700-900nm). Few people pay attention to the composite structure enhanced upconversion luminescence suitable for multiple excitation lights and with perfect absorption characteristics.

[0004] In addition, existing literature (Xu J, Zhao Z, Yu H, et al, Optics Express, 2016, 24, 25742-25751; Zhan S, Wu X, Liu Y, et al, Journal of Alloys and Compounds 2018, 735, 372-376) also reported similar MDM structure resonant cavities. However, in terms of freely adjusting the intensity of the light source absorbed by the resonant cavity, they have the following shortcomings: the intensity of the light irradiated by the MDM structure to the external light source cannot be freely adjusted, and the adjustment spectrum range is relatively narrow.

[0005] In summary, there is an urgent need to develop a new resonant cavity structure to solve the problems existing in the prior art and improve the performance of the device. Summary of the invention

[0006] Based on this, the present invention provides a structure based on an MDM type nanocavity, which includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom; and on each silver nanoring of the silver nanoring layer, two gaps that can be opened or closed freely are symmetrically arranged, and the angle of the gap opening can be adjusted; and the absorption area and the up-conversion fluorescence enhancement factor value in the absorption spectrum can also be adjusted by changing the radius of the silver nanoring. Through the above settings, the MDM type nanocavity can achieve efficient absorption of an external light source with a specific wavelength range, and the MDM type nanocavity has an adjustable absorption spectrum within a specific wavelength range, that is, its absorption spectrum can achieve free absorption intensity adjustment, as well as spectrum redshift or blueshift adjustment, and finally achieve flexible control of the emission spectrum of up-conversion emission.

[0007] The present invention discloses a MDM-type nanocavity structure, which includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom;

[0008] The silver nanoring layer is composed of three silver nanorings with different radii, namely, a silver nanoring inner ring, a silver nanoring middle ring and a silver nanoring outer ring, and the silver nanoring inner ring, the silver nanoring middle ring and the silver nanoring outer ring are concentric rings sharing a common center.

[0009] The silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring are all symmetrically provided with two active gaps, AF respectively, any one of which can be set to an open or closed state, and the active gaps AF are all on the same straight line S, and the straight line S is a straight line passing through the center of the silver nano-ring;

[0010] The silver nano-inner ring, silver nano-middle ring and silver nano-outer ring respond to incident wavelengths of 740-890 nm, 920-1090 nm and 1420-1780 nm respectively.

[0011] The term "response" in the present invention refers to the ability of the MDM nanocavity structure to bind photons of different wavelengths.

[0012] The setting of the above-mentioned gap is more intuitively described in the specification of the present invention. In fact, the two gaps set in the same silver nanoring are symmetrically set, that is, the straight line connecting the two gaps must pass through the shared center of the concentric rings.

[0013] Therefore, the maximum number of gaps that can be opened at the same time is 6, and the minimum number is 0.

[0014] Furthermore, the outer radius of the silver nano-inner ring is in the range of 53-65 nm; the outer radius of the silver nano-middle ring is in the range of 108-120 nm; and the outer radius of the silver nano-outer ring is in the range of 186-198 nm.

[0015] Furthermore, in the silver nanoring layer, the interval between the silver nanoinner ring and the silver nanomiddle ring is 23-47 nm, and the interval between the silver nanomiddle ring and the silver nanoouter ring is 46-70 nm.

[0016] Furthermore, the silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring have the same height and width, the height is 40-70nm, and the width is 10-30nm.

[0017] Furthermore, the thickness of the UCNPs layer is 15-30 nm.

[0018] Furthermore, the dielectric constant of the UCNPs layer is 1.40-1.47.

[0019] Furthermore, the MDM-based nanocavity structure is externally connected to an excitation light source, and the excitation light source continuously irradiates the MDM-based nanocavity structure with irradiation light.

[0020] Furthermore, the wavelength of the irradiation light of the excitation light source is in the range of 700-2000nm.

[0021] Furthermore, the sensitizer used in the UCNPs layer is selected from Nd 3+ , Yb 3+ and Er 3+ One or more of.

[0022] The role of the sensitizer is to sensitize other rare earth ions by providing absorption energy to emit high-energy light. 3+ It has a high absorption coefficient and a large excitation spectrum near 800nm, which can provide sufficient excited state energy, greatly improving the up-conversion luminescence efficiency.

[0023] Similarly, Yb3+ and Er 3+ At 980nm and 1530nm respectively, they are suitable as sensitizers.

[0024] The present invention has the following beneficial effects:

[0025] The invention is based on an MDM type nanocavity structure and can flexibly and quickly achieve the technical effects of multi-band adjustable, perfect absorption and strong local field of the MDM type nanocavity structure by adjusting parameters such as the notch opening angle, the notch opening number, and the radius of the silver nanoring in the silver nanoring layer, thereby providing a new way to enhance the luminous efficiency of up-conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (a) shows a front view of the MDM-type nanocavity structure in Example 1 of the present invention;

[0027] Figure 1 (b) shows a top view of the MDM-type nanocavity structure in Example 1 of the present invention;

[0028] Figure 2 The diagram shows the mechanism of surface plasmon enhanced upconversion luminescence based on the MDM nanocavity structure in Example 1;

[0029] Figure 3 (a) shows the local electric field distribution (|E| in the xz plane) of the overall MDM-type nanocavity structure in Test Example 1;

[0030] Figure 3 (b) shows the near electric field distribution (|E| in the xy plane) of the silver nanoring layer based on the MDM type nanocavity structure in Test Example 1;

[0031] Figure 4 (a) shows the relationship between the change of the notch angle θ based on the MDM type nanocavity structure and the absorption spectrum in Test Example 2;

[0032] Figure 4 (b) shows the relationship between the wavelengths regulated by the three silver nanorings at different notch angles;

[0033] Figure 4 (c) shows the change in absorption rate corresponding to different notch angles θ. DETAILED DESCRIPTION

[0034] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0035] Example 1

[0036] One is based on the MDM type nanocavity structure, which includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom;

[0037] The silver nanoring layer is composed of three silver nanorings with different radii, namely, a silver nanoring inner ring (represented by C1, an outer ring with radius R 1o =59nm), silver nanoring (represented by C2, outer radius R 2o =114nm) and the outer silver nanoring (represented by C3, with an outer radius R 3o =192nm); the inner silver nano ring, the middle silver nano ring and the outer silver nano ring are concentric rings sharing a common center; in the silver nano ring layer, the interval between the inner silver nano ring and the middle silver nano ring is 35nm, and the interval between the middle silver nano ring and the outer silver nano ring is 58nm;

[0038] In the silver nanoring layer, the silver nanoring inner ring, silver nanoring middle ring and silver nanoring outer ring have the same height and width, and their height k is 60nm; their width w is 20nm;

[0039] The silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring are each provided with two active gaps AF, any of which can be set to an open or closed state (the opening angle is set to θ, which can be freely changed between 1 and 15°), and the active gaps AF are all on the same straight line S, which is a straight line passing through the center of the silver nano-ring.

[0040] The silver nano-inner ring, silver nano-middle ring and silver nano-outer ring respond to incident wavelengths of 740-890 nm, 920-1090 nm and 1420-1780 nm respectively.

[0041] The UCNPs layer has a thickness of 25 nm, a dielectric constant of 1.40, and is evenly arranged with a silver bottom layer as a substrate.

[0042] In the silver bottom layer, Px and Py are both 425 nm, and the thickness h of the silver bottom layer is 120 nm.

[0043] An external excitation light source is connected to the MDM-based nanocavity structure, and the excitation light source continuously irradiates the MDM-based nanocavity structure with irradiation light, and the wavelength range of the irradiation light of the excitation light source is 700-2000nm.

[0044] The front view of the MDM nanocavity structure is shown in Figure 1 (a) is shown; the top view is shown Figure 1 (b) as shown.

[0045] Figure 2It shows how the luminescence intensity of UCNPs can be significantly improved based on the MDM nanocavity structure in Example 1. It can be seen from the figure that due to the huge local electric field around the surface plasma of the metal structure and the strong light absorption ability, the upconversion luminescence can be improved by enhancing the absorption process, emission process and energy transfer of rare earth ions. The MDM nanocavity structure based on Example 1 relies on the absorption enhancement mechanism to enhance the absorption of the sensitizer through electric field coupling, while the quantum yield and fluorescence lifetime of UCNPs will not be affected, thereby significantly improving the luminescence intensity of UCNPs.

[0046] The preparation method based on the MDM nanocavity structure is as follows:

[0047] The MDM nanocavity is 2.25 cm 2 The substrate was ultrasonically cleaned in acetone, isopropanol, and deionized water for 15 min and then dried with N2 gas at 423 K. Next, the substrate was heated to 1 × 10 5 A 120 nm silver film was deposited on the substrate under the condition of 100°C to form a silver bottom layer. The same procedure was used to prepare a PFPE stamp with a deposited silver ring (60 nm).

[0048] UCNPs are synthesized by solvothermal method, where the precursor is dissolved in a ligand solution (oleic acid and octadecene) with a higher boiling point, decomposed at high temperature to form crystal nuclei, and then epitaxially grown to prepare UCNPs.

[0049] By adding 1.45wt% of β-NaGdF4:Yb 3+ / Er 3+ A mixed solution of UCNPs dissolved in toluene was spin coated onto the silver film at 3000 rpm for 60 s. The prepared silver-deposited PFPE stamp was applied to the UCNPs layer with precise alignment and appropriate pressure. To transfer the top silver nanoring structure, the UCNPs layer in contact with the stamp was hydrothermally polymerized at 393 K for 30 min at appropriate humidity, and the silver nano-inner ring was applied to the UCNPs layer at a pressure of 0.5 bar. After the first transfer, the PFPE stamp was separated from the UCNPs layer. The second silver nano-middle ring pattern was applied to the UCNPs layer with precise alignment and a pressure of 0.7 bar. Finally, the third silver nano-outer ring was precisely applied to the UCNPs layer and cured by hydrothermal polymerization below 413 K for 1 h at appropriate humidity.

[0050] Example 2

[0051] One is based on the MDM type nanocavity structure, which includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom;

[0052] The silver nanoring layer is composed of three silver nanorings with different radii, namely, a silver nanoring inner ring (represented by C1, an outer ring with radius R 1o =65nm), silver nanoring (represented by C2, outer radius R 2o =120nm) and the outer silver nanoring (represented by C3, with an outer radius R 3o =198nm); the inner silver nano ring, the middle silver nano ring and the outer silver nano ring are concentric rings sharing a common center; in the silver nano ring layer, the interval between the inner silver nano ring and the middle silver nano ring is 25nm, and the interval between the middle silver nano ring and the outer silver nano ring is 48nm;

[0053] In the silver nanoring layer, the silver nanoring inner ring, silver nanoring middle ring and silver nanoring outer ring have the same height and width, and their height k is 70nm; their width w is 30nm;

[0054] The silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring are each provided with two active gaps AF, any of which can be set to an open or closed state (the opening angle is set to θ, which can be freely changed between 1 and 15°, and is set to 6° here), and the active gaps AF are all on the same straight line S, which is a straight line passing through the center of the silver nano-ring.

[0055] The silver nano-inner ring, silver nano-middle ring and silver nano-outer ring respond to incident wavelengths of 720-870 nm, 930-1020 nm and 1460-1610 nm respectively.

[0056] The UCNPs layer has a thickness of 30 nm, a dielectric constant of 1.47, and is evenly arranged with a silver bottom layer as a substrate.

[0057] In the silver bottom layer, Px and Py are both 425 nm, and the thickness h of the silver bottom layer is 120 nm.

[0058] An external excitation light source is connected to the MDM-based nanocavity structure, and the excitation light source continuously irradiates the MDM-based nanocavity structure with irradiation light, and the wavelength range of the irradiation light of the excitation light source is 700-2000nm.

[0059] The above-mentioned preparation method based on the MDM type nanocavity structure is the same as that in Example 1.

[0060] Example 3

[0061] One is based on the MDM type nanocavity structure, which includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom;

[0062] The silver nanoring layer is composed of three silver nanorings with different radii, namely, a silver nanoring inner ring (represented by C1, an outer ring with radius R 1o =53nm), silver nanoring (represented by C2, outer radius R 2o =108nm) and the outer silver nanoring (represented by C3, outer radius R 3o =186nm); the inner silver nano ring, the middle silver nano ring and the outer silver nano ring are concentric rings sharing a common center; in the silver nano ring layer, the interval between the inner silver nano ring and the middle silver nano ring is 45nm, and the interval between the middle silver nano ring and the outer silver nano ring is 68nm;

[0063] In the silver nanoring layer, the silver nanoring inner ring, silver nanoring middle ring and silver nanoring outer ring have the same height and width, and their height k is 40nm; their width w is 10nm;

[0064] The silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring are each provided with two active gaps AF, any of which can be set to an open or closed state (the opening angle is set to θ, which can be freely changed between 1 and 15°, and is set to 6° here), and the active gaps AF are all on the same straight line S, which is a straight line passing through the center of the silver nano-ring.

[0065] The silver nano-inner ring, silver nano-middle ring and silver nano-outer ring respond to incident wavelengths of 960-1130 nm, 1160-1250 nm and 1780-1920 nm respectively.

[0066] The UCNPs layer has a thickness of 30 nm, a dielectric constant of 1.43, and is evenly arranged with a silver bottom layer as a substrate.

[0067] In the silver bottom layer, Px and Py are both 425 nm, and the thickness h of the silver bottom layer is 120 nm.

[0068] An external excitation light source is connected to the MDM-based nanocavity structure, and the excitation light source continuously irradiates the MDM-based nanocavity structure with irradiation light, and the wavelength range of the irradiation light of the excitation light source is 700-2000nm.

[0069] The above-mentioned preparation method based on the MDM type nanocavity structure is the same as that in Example 1.

[0070] Test Example 1

[0071] The absorption peak intensity of the MDM-based nanocavity structure obtained in Example 1 was tested. The specific method is: an external excitation light source is used to continuously irradiate the MDM-based nanocavity structure in Example 1 with irradiation light, the wavelength of the irradiation light covers 700-2000nm, and the intensity of the irradiation light is 340mW. The opening of the gaps of the silver nano-inner ring, silver nano-middle ring and silver nano-outer ring in Example 1 is set to 6°, and the number of gaps opened can be freely adjusted (the gaps of the same silver nano-ring are switched synchronously), so as to monitor the relationship between the number of gaps opened and the absorption intensity of the absorption spectrum based on the MDM-based nanocavity structure. The results are shown in Table 1.

[0072] Table 1 Relationship between the opening of the silver nanoring gap and the integrated area of ​​absorbed light in the absorption spectrum of the MDM-type nanocavity structure

[0073]

[0074] As can be seen from Table 1, in Example 1, as the gaps of the silver nanorings are opened or closed, the number of gaps increases from 0 to 6, and the absorption area of ​​the absorption spectrum shows a trend of first increasing and then decreasing. When the number of openings is 4, the absorption area reaches a maximum value of 457.36, which is due to the three maximum values ​​of the absorption intensity in the spectrum at this time. When the number of gaps is too large, the overall radiation loss of the nanocavity becomes larger, resulting in a decrease in the overall absorption intensity.

[0075] We also tested the local electric field distribution (|E| in the xz plane) based on the overall MDM-type nanocavity structure and the near electric field distribution (|E| in the xy plane) of the silver nanoring layer. The results are as follows: Figure 3 As shown in (a)-(b). Figure 3 (a)-(b) show that the short-wavelength absorption peak is regulated by the inner ring of the silver nanoparticle, while the medium-wavelength and long-wavelength absorption peaks are regulated by the middle and outer rings of the silver nanoparticles, respectively. The absorption peaks of the three bands do not affect each other under effective settings.

[0076] Test Example 2

[0077] Based on Test Example 1, the angle change of the notch opening is further explored. The MDM-based nanocavity structure with 4 notches in Test Example 1 (the notches are located in the middle ring and the outer ring) is selected, and then θ is set to 2°, 4°, 6°, 8° and 10° in sequence, and the effect of the notch angle θ on the absorption peak position is explored.

[0078] The results are as follows Figure 4 (a)-(c) are shown. Figure 4 It can be seen in (a) that as the angle θ effectively increases, the absorption peaks regulated by the middle and outer rings (located at medium and long wavelengths, respectively) undergo an obvious blue shift, while the absorption peak corresponding to the inner ring (located at short wavelength) remains unchanged. Figure 4 (b) shows the relationship between the wavelengths of the three rings under different notch angles. It can be seen that when the angle θ increases, the wavelengths corresponding to the middle ring and the outer ring gradually decrease, while the wavelength corresponding to the inner ring remains basically unchanged; Figure 4 (c) shows the change in absorption rate due to different notch angles θ. As the angle θ increases, the value generally shows a downward trend, but the overall absorption rate still remains high at more than 92%.

[0079] Figure 4 (a)-(c) can prove that the setting of θ can effectively control the absorption peaks generated by the middle ring and the outer ring.

[0080] Test Example 3

[0081] In this test example, when the MDM nanocavity structure in Example 1 is connected to an external excitation light source, the radius of the silver nano-inner ring, the silver nano-middle ring, and the silver nano-outer ring are changed respectively (at this time, the radius of the other two silver nano-rings remains unchanged as the initial value described in Example 1), based on the change of the absorption spectrum of the MDM nanocavity structure and the enhancement of the fluorescence emission spectrum. The test method is: by setting the change of the radius of the top three silver nano-rings of the MDM nanocavity structure, the absorption spectrum of the MDM nanocavity is obtained under the irradiation of the excitation light source, and the local electric field distribution under this condition is tested, so as to calculate the fluorescence enhancement factor of UCNPs. The results are shown in Table 2.

[0082] Among them, EF upc represents the fluorescence enhancement factor of upconversion luminescence, and its calculation formula is:

[0083] EF upc ≈∣E / E0∣ 4

[0084] Where E0 and E are the electric field intensity of the excitation light source and the local electric field intensity of the MDM nanocavity, respectively.

[0085] Table 2 Changes in the absorption spectrum and enhancement of the fluorescence emission spectrum based on the MDM nanocavity structure when the radius of the silver nanoinner ring (C1), silver nanomiddle ring (C2) and silver nanoouter ring (C3) are changed respectively

[0086] Table 2 Relationship between the integral area of ​​absorbed light and the fluorescence enhancement factor in the absorption spectrum corresponding to different silver nanoring radii

[0087]

[0088]

[0089] As can be seen from Table 2, with the effective increase of the radius of the silver nanoring, the absorption area of ​​the absorption spectrum shows an increasing trend, and the absorption area and the radius are approximately positively correlated. This is because the effective length of the silver nanoring increases; while EF upc It shows a trend of increasing first and then decreasing, and 1o =53nm, R 2o =114nm and R 3o =192nm, the upconversion fluorescence enhancement factor values ​​reach the maximum, which shows that by adjusting the radius of the silver nanoring, the absorption area and the conversion fluorescence enhancement factor value in the absorption spectrum can be adjusted.

[0090] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0091] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A MDM-type nanocavity structure, characterized in that: The MDM type nanocavity structure includes a silver nanoring layer, a UCNPs layer, and a silver bottom layer from top to bottom; The silver nanoring layer is composed of three silver nanorings with different radii, namely, a silver nanoring inner ring, a silver nanoring middle ring and a silver nanoring outer ring, and the silver nanoring inner ring, the silver nanoring middle ring and the silver nanoring outer ring are concentric rings sharing a common center. The silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring are all symmetrically provided with two active gaps, AF respectively, any one of which can be set to an open or closed state, and the active gaps AF are all on the same straight line S, and the straight line S is a straight line passing through the center of the silver nano-ring; The silver nano-inner ring, silver nano-middle ring and silver nano-outer ring are responsive to incident wavelengths of 740-890 nm, 920-1090 nm and 1420-1780 nm, respectively; The opening angle of the active notch AF is 1-15°; The outer radius of the silver nano inner ring is in the range of 53-65 nm; the outer radius of the silver nano middle ring is in the range of 108-120 nm; and the outer radius of the silver nano outer ring is in the range of 186-198 nm.

2. According to claim 1, the MDM nanocavity structure is characterized in that: In the silver nanoring layer, the interval between the silver nanoinner ring and the silver nanomiddle ring is 23-47 nm, and the interval between the silver nanomiddle ring and the silver nanoouter ring is 46-70 nm.

3. According to claim 1, the MDM-type nanocavity structure is characterized in that: The silver nano-inner ring, the silver nano-middle ring and the silver nano-outer ring have the same height and width, the height is 40-70nm, and the width is 10-30nm.

4. According to claim 1, the MDM-type nanocavity structure is characterized in that: The thickness of the UCNPs layer is 15-35 nm.

5. The MDM-type nanocavity structure according to claim 1, characterized in that: The dielectric constant of the UCNPs layer is 1.40-1.

47.

6. The MDM-type nanocavity structure according to claim 1, characterized in that: The MDM-based nanocavity structure is externally connected to an excitation light source, and the excitation light source continuously irradiates the MDM-based nanocavity structure with irradiation light.

7. The MDM-type nanocavity structure according to claim 6, characterized in that: The wavelength of the irradiation light of the excitation light source is in the range of 700-2000nm.

8. The MDM-type nanocavity structure according to claim 4, characterized in that: The sensitizer used in the UCNPs layer is selected from Nd 3+ , Yb 3+ and Er 3+ One or more of.

Citation Information

Patent Citations

  • Adjustable near-infrared band plasma bi-induction transparent nanometer device

    CN105759353A

  • Plasmon resonance wavelength tuner based on metal broken nanometer double-ring structure

    CN114296165A